African proverbs for Cultural Education: A Step towards Digital Archiving - Adom, Dickson; Chukwuere, Joshua Ebere; Addo, Irene Appeaning; Tabi-Agyei, Emmanuel; Thulla, Philip Foday Yamba (Journal of History Culture and Art Research, 2021)
African proverbs, considered as the most ubiquitous genre of folklore, are instructional vehicles through which the cultural values in African societies are imparted to generations. This phenomenology study was carried out to offer a roadmap for categorising and interpreting African proverbs using the Ethnopragmatic method while investigating the possibility of developing a user-friendly mobile app for it. Face-to-face interviews, focus group discussions, telephone and skype interviews were used as data collection instruments for the study. Eighty-eight respondents sampled using the purposive and snowball sampling techniques were recruited for the study from three African countries. The findings revealed that creating a user-friendly mobile app on African proverbs holds great potential in assisting in their digital documentation and preservation for posterity. Moreover, the scholarly categorisation and interpretation of African proverbs were seen as crucial to the preservation of this indispensable genre. The study recommends that African governments, ministries of education, cultural institutions and media houses must assist research efforts aimed at cultural preservation and propagation of the philosophical insights in African proverbs.